Influence of Ligand Isomerism on the Photophysical Properties of AIPE-Active Rhenium(I) Complexes: Investigations with a 2-(1,2,3-Triazol-1-yl)pyridine (Tapy)-Based Complex and Its Triazolylidene Derivatives - Abanoub Mosaad Abdallah; Mariusz Wolff; Nadine Leygue; Maëlle Deleuzière; Nathalie Saffon-Merceron; Charles-Louis Serpentini; Eric Benoist; Suzanne Fery-Forgues (Molecules)
Due to their rare properties of solid-state luminescence enhancement (SLE), tricarbonylrhenium complexes are promising candidates for applications as photoluminescent materials. However, the effect of isomerism on optical properties is still not well known. The aim of this in-depth study is to explore the behavior of a 2-(1,2,3-triazol-1-yl)pyridine (tapy) complex and compare it with that of the isomers studied previously. Two derivatives that incorporate a mesoionic carbene ligand and represent an emerging class of molecules were also synthesized and compared with the corresponding isomers. The crystallographic data revealed that compounds in the solid state have little or no π–π interactions. The spectroscopic study was supported by DFT calculations. All the compounds were weakly phosphorescent in solution but exhibited a marked SLE effect. The Re-Tapy complex is an excellent solid-state emitter (PLQY = 0.62), well suited for applications related to aggregation-induced phosphorescence emission (AIPE). Its sensitivity to mechanical stimuli was unprecedented among the isomers considered to date. On the other hand, triazolylidene complexes are less emissive than their pyta(1,2,3) counterparts. This study shows how the ligand isomerism influences the optical properties of tricarbonylrhenium(I) complexes. It indicates that selecting the right pattern is a key factor for the design of efficient photoluminescent materials.